2018
DOI: 10.1177/0954406218802310
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of cavitation in the draft tube of Francis turbine model by J-Groove

Abstract: Cavitation is recognized as a phenomenon that can cause serious damage to a hydro turbine and can reduce its performance when operating at off-design point. This is an undesired phenomenon, which needs to be improved. In order to suppress the cavitation in the Francis turbine draft tube, a technology with grooved draft tube named J-Groove is introduced in the Francis turbine. The Francis turbine performance and the internal flow characteristic are investigated both with and without J-Groove installation by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The CFD analysis process is directly connected to the optimum design process. The CFD analysis method was adopted from previous studies [33][34][35].…”
Section: Cfd Methodologymentioning
confidence: 99%
“…The CFD analysis process is directly connected to the optimum design process. The CFD analysis method was adopted from previous studies [33][34][35].…”
Section: Cfd Methodologymentioning
confidence: 99%
“…The swirling flow was eliminated by controlling the angular momentum of flow by using the hollows named j-grooves. The jgroove structures were also explored by Wei et al, [3] and Chen and Choi [4]. It was observed that the structures decreased the quantity of vortex structures.…”
Section: Introductionmentioning
confidence: 97%
“…The pressure pulsations in the leafless region all show a dynamic and static interference phenomenon, and the main frequency is the blade passing frequency. Chen et al , considered the impact of J-Groove on pressure pulsation at nondesign operating points through experimental methods and numerical simulations. The results show that J-Groove can improve performance and reduce internal unsteady flow.…”
Section: Introductionmentioning
confidence: 99%